The bingo project: the regulation of bingo in England and Wales, Canada, Brazil and online in the European Union 2013-2017 - Bedford, Katharine (UK Data Service, 2018)
The data collection contains anonymised transcripts of interviews with people involved in land-based bingo in England and Wales, Brazil, and Canada, and within online bingo in the European Union. The interviews cover the way that rules were experienced. The collection also includes a survey of bingo industry insiders in England and Wales, on their priorities for law and policy change. The project seeks to make a substantial contribution to debates about gambling and the regulation of speculation by researching bingo. Bingo is a markedly under-researched site, attracting a fraction of the attention given to casinos. However it is a globally significant and profitable gambling form, played in many countries and increasingly popular online. Bingo is also enmeshed with law and political economy in distinctive ways. It is a key site for charitable fundraising in many jurisdictions, and it is often associated with community and social welfare. This legal and social position, at the intersection of risk and welfare, poses significant challenges for regulators, and raises important questions about how the governance of speculation is related to concerns about social cohesion and non-profit activity. The proposed research will address those regulatory challenges, and provide answers to those key questions. Using four case studies of bingo regulation (England and Wales, Canada, Brazil, and online play offered to residents of EU countries), the research will provide a systematic account of how bingo is regulated, to ascertain the key legal and policy challenges involved, and to make recommendations to policymakers, the gambling industry, third-sector stakeholders, and academics.